$L^∞$ Convergence of TRUNC Element for the Biharmonic Equation (Journal of Computational Mathematics, 1997)
The paper considers the $L^∞$ convergence for TRUNC finite elements solving the boundary value problems of the biharmonic equation. The nearly optimal $L^∞$ estimates for the error of first order derivatives are given.